Assessing physical activity, fruit and vegetable intake and sugar-sweetened beverage consumption patterns of college students - Opoku-Acheampong, Audrey Anima (Kansas State University, 2014)
Objective: The aims of this study were to test the effectiveness of a 15-month intervention in reducing sugar-sweetened beverage (SSB) consumption among college students and to assess fruit and vegetable intake and physical activity habits and their relationship to SSB consumption in order to improve health outcomes. Design: Randomized, controlled study. Participants: One hundred and fifty-six college students (18-24 y) from a Midwestern university, primarily female (72%), white (89%) and freshmen (51%). Intervention: Participants were randomized to control and intervention groups. Participants in the control group received no information on healthful behaviors. The intervention occurred in two stages: 1) Participants received three stage-tailored messages on healthful behaviors weekly for 10 weeks; 2) After the 3-month physical assessment, participants received 3 stage-tailored messages monthly and one email encouraging them to visit the portal page. Main Outcome Measure(s): Stages of Change for physical activity and fruit and vegetable intake; self-reported physical activity scores, self-reported fruit and vegetable intake and SSB consumption habits. Analysis: Changes in SSB consumption patterns were determined using generalized linear mixed models and linear regression models tested associations between fruit and vegetable intake, physical activity and SSB consumption. Linear mixed models were used to explore relationship between stage of change and fruit and vegetable intake and physical activity. Results: The 15-month intervention did not significantly reduce SSB consumption in the intervention group (p > 0.05). Participants recorded low fruit and vegetable intake and moderate physical activity scores. Conclusions and Implications: The high SSB consumption and low fruit and vegetable intake observed could increase students’ risk for weight gain and obesity-related conditions. Thus, college campuses can help student maintain physical activity behavior while helping them to improve their eating habits.
Keywords: College students; Overweight; Dietary habits; Physical activity habits; Nutrition (0570); Public Health (0573)